Workplace Bullying in Italy: A Systematic Review and Meta-Analysis - Colaprico, Corrado; Grima, Daniela; Shaholli, David; Imperiale, Ilaria; La Torre, Giuseppe (La Medicina del Lavoro, 2023)
Background: Within any work environment, employees may be affected by “workplace bullying”, a form of violent and repeated social behavior towards subordinates and colleagues. This review aimed to investigate the prevalence of bullied workers in Italy, the causes of the phenomenon, and the consequences at physical, psychological, and organizational levels. Methods: We included observational studies and systematic reviews examining the prevalence of bullied workers and the causes and consequences in Italian workplaces. Data extraction and analysis were performed on all included studies. The research strategy included three electronic databases (PubMed, Scopus, and Web of Science). A comprehensive search was done to retrieve articles based on a PRISMA-compliant protocol registered in PROSPERO: CRD 42023394635. Results: One hundred eighty-four articles were retrieved, and once duplicates and irrelevant articles were removed, 42 useful articles were reviewed. The mean pooled prevalence, calculated based on workers complaining of mistreatment, was 6.7% (SD: 4,09) and increased significantly to 17.0% (SD: 12.88) when considering only healthcare workplaces. Causes include how impaired mental health and high workload reinforce the possibility of being bullied in the workplace, resulting in a worsening of the worker's quality of life (physical and psychological) and the work organization with increased absenteeism and job changes. Conclusions: Workplace bullying is a very present phenomenon within workplaces in Italy. In light of this, it is necessary to put prevention plans in place and find solutions to maintain optimal organizational well-being in the work environment.